Diagnostic Investigation of Lesions Associated with Succinate Dehydrogenase Defects - Taïeb, David; Timmers, Henri; Pacak, Karel (Hormone and Metabolic Research, 2018)
The mitochondrial enzyme succinate dehydrogenase (SDH) acts as a tumor suppressor. Biallelic inactivation of one of the genes encoding for SDH subunits (collectively named SDHx) leads to complete loss of the protein function and the development of diverse group of tumors. Pheochromocytomas-paragangliomas are the prime example of hereditary tumors caused by SDH deficiency. In this review, we discuss the roles of imaging examinations, and illustrate new insights into genotype-imaging phenotype relationships.
Keywords: positron emission tomography; gallium radioisotopes; 6-(18F)fluoro-l-3; 4-dihydroxyphenylalanine; precision medicine; theranostics; succinate dehydrogenase